1998
DOI: 10.1046/j.1365-3083.1998.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Denaturation of Egg‐White Proteins Abrogates the Induction of Oral Tolerance of Specific Th2 Immune Responses in Mice

Abstract: Human foods are usually prepared by cooking. Boiling of chicken egg-white (EW) led to decreased allergenicity, and abrogated intestinal uptake of immunoreactive ovalbumin (OVA) when fed to mice. Therefore, the effects of oral administration of boiled EW were examined further in BALB/c mice. Specific IgE, IgG 1 and IgG antibody responses were suppressed by raw EW, but not by EW boiled for 5 or 60 min, fed prior to sensitization with 10 mg OVA or 1 mg DNP-OVA in alum. Similar results were obtained when mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…Bu et al [14 ]indicated that fermentation with lactic acid bacteria could significantly reduce the antigenicity of α-LA and β-LG in skim milk; combined strains of Lactobacillus helveticus and Streptococcus thermophilus were even more effective. The influence of heat treatment and enzymatic digestion on the allergenicity of purified egg proteins either alone or in combination has been described by other investigators [12]. Our data reveal that Chinese traditional cooking approaches can also reduce the allergenicity of egg protein and thus represent a novel pathway to modulate the allergenicity of food allergens.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Bu et al [14 ]indicated that fermentation with lactic acid bacteria could significantly reduce the antigenicity of α-LA and β-LG in skim milk; combined strains of Lactobacillus helveticus and Streptococcus thermophilus were even more effective. The influence of heat treatment and enzymatic digestion on the allergenicity of purified egg proteins either alone or in combination has been described by other investigators [12]. Our data reveal that Chinese traditional cooking approaches can also reduce the allergenicity of egg protein and thus represent a novel pathway to modulate the allergenicity of food allergens.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, most of the endeavors were unsuccessful [12]. It was reported that protein from processed egg was significantly lower than that of raw egg [13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential sources of protein interaction, only a few allergens do not survive processing. Heat treatment has been recognized as a way of reducing allergenicity and boiled hen's egg has been reported as less allergenic [25]. However, severe food hypersensitivity reactions are also described for heat treated hen's egg [6].…”
Section: Introductionmentioning
confidence: 99%
“…As indirect proof that heat-denatured proteins are not allergenic, Peng et al reported that heat-denaturation of egg white proteins abrogated the induction of oral tolerance of specific Th2 immune responses in mice. 13) On the other hand, Urisu et al reported that 37 of 38 subjects (97%) who immediately manifested positive reactions to freeze-dried egg white did not respond to heated egg white in double-blind, placebo-controlled tests. 14) It is unclear how heat-coagulated proteins digested in the gastrointestinal tract and hydrolyzed peptides, with or without allergenic activity, are absorbed into portal blood.…”
mentioning
confidence: 99%